Building close and long-lasting relationships with focal customers: an empirical study of seed potato purchasing by Filipino potato farmers - Batt, Peter (Curtin University, 2003)
In the highlands of the Northern Philippines, a model of long-term relationships between potato farmers and their preferred seed suppliers is proposed. In the absence of any certified seed system that might provide some guarantee of seed quality, farmers prefer to transact with those seed suppliers with whom they have had some favourable prior experience. Such suppliers provide both the best quality seed and, since most farmers must borrow the capital to purchase the seed, the most favourable terms of repayment. As there is much uncertainty in the exchange, the farmer's relationship with their preferred seed supplier is based on trust. However, since the farmer's satisfaction with the exchange cannot be ascertained until after purchase, trust is antecedent to satisfaction. As satisfaction is derived from the economic benefits the farmer obtains, satisfaction will lead to the farmer's desire to maintain the relationship. Satisfaction is enhanced both by the seed supplier's willingness to extend credit and to provide information. As there is much variation between alternative seed supplier's offer quality, satisfaction will result in the farmer becoming more dependent upon that seed supplier who makes the best offer. Furthermore, having provided the farmer with financial assistance, seed suppliers will find that they have constrained their opportunities to use coercive influence strategies, for in the absence of any formal contract, farmer's may readily default on the loan. The use of coercive influence strategies will reduce both the farmer's trust in their preferred seed supplier and the farmer's desire to maintain the relationship.While trust is more important in the transitional economies, critical problems emerge with the use of standardised item measures and scales developed in the industrial countries. Cultural specific adjustments are necessary to ensure social constructs such a trust are functionally equivalent. However, in the context of long-term relationships where satisfaction is also cumulative, introducing measures of both economic and social satisfaction have the potential to overlap with the generally accepted measures of trust.